PENGEMBANGAN SUMBER DAYA MANUSIA PEMERINTAHAN DESA DALAM TEKNIS PEMBUATAN SURAT KEPUTUSAN DI KABUPATEN INDRAMAYU - Gunardi Gunardi; Rasji Rasji (Jurnal Bakti Masyarakat Indonesia, 2022)
The village government has the duty and authority to regulate and manage village government affairs. The goal is that the village government is able to carry out village government affairs well, so that the village government can create the welfare of the village community. Likewise, the village government in Indramayu Regency is obliged to carry out these duties and authorities. One of the important aspects that must be possessed by village government officials is their ability to make various decisions related to the implementation of their duties and authorities and to solve various problems they face. The village government in Indramayu Regency still does not understand technically the correct and appropriate decision making in accordance with applicable regulations. What are the efforts to develop village government human resources so that they are technically able to make decisions properly and correctly? That is the problem that the village government needs to overcome through community service activities with the theme "Development of village government human resources in technical decision making in Indramayu Regency". The goal is that village government officials are able to make decisions properly and correctly. The method used is the lecture method and technical guidance in making decision letters. The results of community service activities show that village government resources are increasingly understanding and able to make decisions properly and correctly in accordance with applicable regulations. The conclusion is that this activity has been able to develop the human resource capacity of the village government apparatus, so that the village apparatus is able to make decisions properly and correctlyABSTRAK:Pemerintah desa mempunyai tugas dan wewenang untuk mengatur dan mengurus urusan pemerintahan desa. Tujuannya adalah agar pemerintah desa mampu menjalankan urusan pemerintahan desa dengan baik, agar pemerintahan desa dapat menciptakan kesejahteraan masyarakat desa. Demikian juga pemerintah desa di Kabupsten Indramayu wajib melaksanakan tugas dan wewenang tersebut. Salah satu aspek penting yang harus dimiliki oleh aparatur pemerintah desa adalah kemampuannya untuk membuat berbagai keputusan  yang berkaitan dengan pelaksanaan tugas dan wewenangnnya serta untuk menyelesaikan berbagai permasalahan yang dihadapinya. Pemerintah desa di Kabupaten Indramayu masih belum memahami secara teknis pembuatan surat keputusan yang benar dan tepat sesuai dengan peraturan yang berlaku. Bagaimana upaya pengembangan sumber daya manusia pemerintahan desa agar secara teknis mampu membuatan surat keputusan dengan baik dan benar? Itulah permasalahan yang perlu atasi oleh pemerintah desa melalui kegiatan pengabdian kepada masyarakat dengan tema “pengembangan sumber daya manusia pemerintahan desa dalam teknis pembuatan surat keputusan di Kabupaten indramayu”. Tujuannya adalah agar aparatur pemerintahan desa mampu membuat surat keputusan dengan baik dan benar. Metode yang digunakan adalah metode ceramah dan pembimbingan secara teknis pembuatan surat keputusan. Hasil kegiatan pengabdian kepada masyarakat menunjukan sumber daya pemerintah desa makin memahami dan mampu membuat surat keputusan secara baik dan benar sesuai dengan peraturan yang berlaku. Kesimpulannya adalah kegiatan ini telah mampu mengembangkan kemampuan sumber daya manusia aparatur pemerintahan desa, sehingga aparatur desa mampu membuat surat keputusan dengan baik dan benar.